Wirtschaftliche Entwicklung oder evolutorischer Wandel. Ein integrativer Versuch zur Fundierung der evolutorischen Ökonomik. - Fritz Rahmeyer (Universität Augsburg, Institut für Volkswirtschaftslehre, 2005)
In two survey articles on evolutionary economics Hodgson points out that currently a consensus of opinion concerning the meaning and explanation of economic evolution does not exist. But most of the authors involved agree that the common characteristic of its subject is the central importance of endogenously emerging innovation activity of privately owned enterprises, causing a structured economic and organizational change. Compared with that, there is a lively dispute regarding the question if processes of technical and economic change can be explained analogously to the basic principles of biological evolution. From an economic point of view Schumpeter and Marshall, geared to the level of a single firm, are of great importance for the development of an evolutionary theory of economic change. The path-breaking approach of Nelson and Winter, also based on the significance of innovation activities of firms, but on their behaviour as well, points the way to a micro foundation of evolutionary change and its potential applications, for instance the theory of the firm and Schumpeterian competition. So, after the exposition of Schumpeter and Marshall on discontinous or gradual economic development, a concept of economic evolution following Neo-Darwinian biological evolution is worked out in detail. In that as a result the idea of ?Universal Darwinism? is the focus of interest. A population of firms instead of a single firm comes to the fore, according to population thinking in biology. In enlarging the Schumpeter-Marshall model finally an evolutionary theory of innovation activity will be elaborated.
urn:nbn:de:bvb:384-opus4-711609
Keywords: O31; B52; B30; 330; Marshall and Schumpeter; Biological and Economic Evolution; Innovation Activity